Power in numbers : the political strategy of protest and rebellion - DeNardo, James, 1949- (Princeton, New Jersey : Princeton University Press, 1985)
This book explores the logic of struggle between radical movements and incumbent regimes, and develops a general theory of strategy in protests, uprisings, and rebellions. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- CONTENTS -- LIST OF ILLUSTRATIONS -- FOREWORD / Converse, Philip E. -- ACKNOWLEDGMENTS -- INTRODUCTION -- ONE. History and Strategy in Theories of Revolution -- TWO. A Formal Model o'f Protest and Rebellion -- Appendix A.A Note on the Free-Rider Problem -- THREE. The Logic of Peaceful Protest -- Appendix B. Strategy-Potential Curves -- FOUR. Pragmatists and Purists -- FIVE. Reformers and Revolutionaries -- SIX. Moderates and Radicals -- SEVEN. Organization and Strategy -- EIGHT. Repression -- NINE. The Political Strategy of Violent Disruption -- TEN. The Logic of Terrorism -- ELEVEN. Violence and Factionalism -- INDEX.
Includes bibliographical references and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Government, Resistance to; Revolutions; Résistance au gouvernement; Révolutions.; revolutions; POLITICAL SCIENCE -- General; Government, Resistance to; Revolutions; Protestbewegingen; Verzet